2017
DOI: 10.1111/acer.13359
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Reduces Ethanol Self‐Administration in Mice

Abstract: Background Excessive ethanol consumption remains an important health concern and effective treatments are lacking. The central oxytocin system has emerged as a potentially important therapeutic target for alcohol and drug addiction. These studies tested the hypothesis that oxytocin reduces ethanol consumption. Methods Male C57BL/6J mice were given access to ethanol (20% v/v) using a model of binge-like drinking (“drinking-in-the-dark”) that also included the use of lickometer circuits to evaluate the tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 38 publications
4
52
2
2
Order By: Relevance
“…In more recent reports, systemic administration of oxytocin has been shown to reduce alcohol preference and intake in a variety of voluntary drinking models in rats (Bowen, Carson, Spiro, Arnold, & McGregor, 2011; MacFadyen et al, 2016; McGregor & Bowen, 2012) and mice (King et al, 2017; Peters, Slattery, Flor, Neumann, & Reber, 2013). Specifically, McGregor and Bowen (2012) found that a single dose of oxytocin (1mg/kg) produced a long-lasting reduction in preference for an alcohol-containing solution compared with a nonalcoholic sweet solution.…”
Section: Oxytocin Effects On Preclinical Models Of Addictionmentioning
confidence: 99%
See 2 more Smart Citations
“…In more recent reports, systemic administration of oxytocin has been shown to reduce alcohol preference and intake in a variety of voluntary drinking models in rats (Bowen, Carson, Spiro, Arnold, & McGregor, 2011; MacFadyen et al, 2016; McGregor & Bowen, 2012) and mice (King et al, 2017; Peters, Slattery, Flor, Neumann, & Reber, 2013). Specifically, McGregor and Bowen (2012) found that a single dose of oxytocin (1mg/kg) produced a long-lasting reduction in preference for an alcohol-containing solution compared with a nonalcoholic sweet solution.…”
Section: Oxytocin Effects On Preclinical Models Of Addictionmentioning
confidence: 99%
“…MacFadyen et al (2016) reported that systemic administration of a lower dose range of oxytocin (0.1–0.5mg/kg; ip) reduced operant alcohol self-administration in rats. Further, in alcohol-preferring C57BL/6J mice, systemic administration of oxytocin decreased alcohol self-administration and binge-like alcohol consumption in a dose-related manner (0.3, 1, 3 or 10 mg/kg; ip), as well as reduced motivation for alcohol reward as measured by responding under a PR schedule (King et al, 2017). Peripheral oxytocin treatment in a similar dose range (1–10mg/kg) reduced alcohol consumption in male and female prairie voles that had two-bottle choice free-access to 15% alcohol (Stevenson, Wenner, et al, 2017).…”
Section: Oxytocin Effects On Preclinical Models Of Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, systemic administration of oxytocin reduces alcohol preference and intake in a variety of drinking models in rats (Bowen et al, 2011; MacFadyen et al, 2016; McGregor and Bowen, 2012) and mice (King et al, 2017; Peters et al, 2013). Direct injection of oxytocin into brain ventricles reduced alcohol consumption and alcohol-induced dopamine efflux in the nucleus accumbens in rats (Peters et al, 2016).…”
Section: Mechanisms Underlying Chronic Alcohol Stress and Drinkimentioning
confidence: 99%
“…Better understanding of the factors that influence renewed drug-seeking, and the persistent craving for drugs, is needed. Studying mouse models of extinction and relapse may help identify molecular mechanisms of brain plasticity in drug addiction [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%